2014
DOI: 10.1038/srep06033
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of membrane nanosurface of red blood cells under hemin action

Abstract: Hemin is the product of hemoglobin oxidation. Some diseases may lead to a formation of hemin. The accumulation of hemin causes destruction of red blood cells (RBC) membranes. In this study the process of development of topological defects of RBC membranes within the size range from nanoscale to microscale levels is shown. The formation of the grain-like structures in the membrane (“grains”) with typical sizes of 120–200 nm was experimentally shown. The process of formation of “grains” was dependent on the hemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 27 publications
4
33
0
3
Order By: Relevance
“…Second, denaturation of hemoglobin (Hb) can cause the damage. Accumulating evidence has shown that released hemin, one of the end product of Hb denaturation, is a potent catalyst of lipid peroxidation, which in turn causes hemolysis [27][28][29]. Many microscopy studies have shown that hemin can affect the conformation of the cell cytoskeleton, which in turn affects the cell structure [27,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Second, denaturation of hemoglobin (Hb) can cause the damage. Accumulating evidence has shown that released hemin, one of the end product of Hb denaturation, is a potent catalyst of lipid peroxidation, which in turn causes hemolysis [27][28][29]. Many microscopy studies have shown that hemin can affect the conformation of the cell cytoskeleton, which in turn affects the cell structure [27,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…To characterize the membrane topology of nanosurface the spatial Fourier analysis was used to decompose the image of the membrane surface into three constituents based on space periods of membrane patterns revealed by AFM. This methodological approach was proposed and described in detail in our previous studies [10,15] and also is used now the by other authors in study of membrane nanosurface [12].…”
Section: Atomic Force Microscopymentioning
confidence: 99%
“…We build profiles in defined sections and measured the spatial period (L) of the membranes nanosurfaces. Detailed the procedure of the study was presented earlier in [14,15]. Nanosurfaces of PRBC membranes and their profiles on days 2, 9, and 30 of storage are shown in Figs.…”
Section: Parameters and Structure Of Defectsmentioning
confidence: 99%
“…By day 30, the population of echinocytes decreased to 15±4%, while the level of spheroechinocytes reached 83±16%. These erythrocyte forms could emerge as a result of changes in the redox processes in the erythrocyte [5] and hemoglobin polymerization inside the cells [14]. Partial release of hemoglobin from the cells, erythro cyte "leakage", was observed on days 23-30 of storage (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was virtually amply determined by the erythrocyte leakage (no burst erythrocytes or their shadow were observed in the solution). The most possible cause of leakage was membrane destructions a result of hemoglobin coagulation and polymerization in the cell [14]. Leakage started on days 16-23 of storage, when the level of lemon-shaped ovalocytes was the maximum ( Table 1).…”
Section: Resultsmentioning
confidence: 99%